Marriage-based pilot clean household fuel intervention in India for improved pregnancy outcomes. Issue 10 (5th October 2020) - Pillarisetti, Ajay; Roy, Sudipto; Diamond-Smith, Nadia; Ghorpade, Makarand; Dhongade, Arun; Balakrishnan, Kalpana; Sambandam, Sankar; Patil, Rutuja; Levine, David I; Juvekar, Sanjay; Smith, Kirk R
Abstract : Introduction: Health interventions often target pregnant women and their unborn children. Interventions in rural India targeting pregnant women, however, often do not cover the critical early windows of susceptibility during the first trimester and parts of the second trimester. This pilot seeks to determine if targeting newlyweds could protect entire pregnancies with a clean stove and fuel intervention. Methods: We recruited 50 newlywed couples who use biomass as a cooking fuel into a clean cooking intervention that included a liquefied petroleum gas (LPG) stove, two gas cylinders, a table to place the stove on and health education. We first evaluated whether community health workers in this region could identify and recruit couples at marriage. We quantified how many additional days of pregnancy could be covered by an intervention if we recruited at marriage versus recruiting after detection of pregnancy. Results: On average, we identified and visited newlywed couples within 40 (SD 21) days of marriage. Of the 50 couples recruited, 25 pregnancies and 18 deliveries were identified during this 1-year study. Due to challenges securing fuel from the LPG supply system, not all couples received their intervention prior to pregnancy. Regardless, couples recruited in the marriage arm had substantially more days with the intervention than couples recruited into a similar arm recruited at pregnancy (211 SD 46 vs 120 SD 45). At scale, a stove intervention targeting new marriages would cover about twice as many weeks of first pregnancies as an intervention recruiting after detection of pregnancy. Conclusions: We were able to recruit in early marriage using existing community health workers. Households recruited early in marriage had more days with clean fuel coverage than those recruited at pregnancy. Our findings indicate that recruitment at marriage is feasible and warrants further exploration for stove and other interventions targeting pregnancy-related outcomes.